Enhancement of Indonesian Junior High School Student Creative Thinking Skills Through a STEM-Project Based Learning: A Case Study of Quasi-Experimental Evidence - Purmanna, Astrino; Suwono, Hadi; Sueb, Sueb; Raharjo, Sigit (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The main vision of education, especially in learning natural sciences must be able to develop student creative thinking skills. Creative thinking has a position that is as important as understanding concepts, so this encourages researchers to look for learning processes and learning environments that are able to encourage students to creative thinking. The purpose of this study is to analyze the effect Project Based Learning through a science, technology, engineering and math (STEM) education approach on creative thinking skills. This research was a case study of quasi-experimental with a nonrandomized control-group pretest-posttest design. Research samples were 109 Indonesian junior high school student, which comprises one experiment class group and one control class group determined by a cluster random sampling technique. The data collection instrument was in the form of creative thinking skills essay questions. The research data were analyzed using Quade's Rank Analysis of Covariance because the research data did not meet the normality test requirements. The results of the study show that class using STEM-PjBL learning are significantly better at creative thinking skills when compared to class using Problem-Based Learning model. This research contributes to providing innovative alternative learning information in order to empower junior high school students' creative thinking skills.